P05.37 Hypofractionated radiosurgery for benign skull base tumors. (19th September 2018) - Daniel, R; Hamisch, C; Grau, S; Jablonska, K; Baues, C; Kocher, M; Treuer, H; Ruge, M
Abstract: Background: The use of single fraction stereotactic radiosurgery (SRS) is limited by tumour size (>3cm) and/or close proximity to critical structures (e.g. cranial nerves/optical pathway/pituitary gland). Here we present data using hypofractionated SRS (hSRS) for the treatment of benign skull base tumors either > 3 cm and/or neighboring critical structures. Material and Methods: In this single center retrospective analysis we consecutively included all patients with benign skull base tumors (meningeomas, nonsecreting pituitary adenomas, schwannomas) who underwent Cyberknife® hSRS using a tumor surface dose of 25 Gy applied in five fractions (isodose level 70–80%) between 2012 and 2016 with a minimum follow-up of 6 months. Patient data were analyzed in terms of tumor control (defined as no further intervention required), symptom control (stable clinical condition) and incidence of early and late treatment related complications (rated by using the Common Terminology Criteria for Adverse Events, CTCAE; v4.03). Results: 33 patients (f:m = 20:13, median age = 58 years) were treated with hSRS. Tumor entities were meningiomas (n=22), pituitary adenomas (n=8), vestibular- (n=1) and trigeminal nerve schwannomas (n=2). 42% underwent surgery prior hSRS. Mean tumor volume was 9.4 ml (0.6–35 ml). Median follow-up was 23 months (6–52 months). The actuarial 1-, 2-, and 4-year tumor control rate was 100%, 94.5% and 94.5%, respectively. Symptoms improved in 38% (n=8) of symptomatic cases (n=21). Transient adverse events (CTCAE grade I and II) were observed in 9% of the cases (headache n=1, arm paresis n=1, partial alopecia n=1). No permanent adverse events were observed. Conclusion: Our treatment results show low rates of mild adverse events and encouraging tumor control rates which are consistent with those reported in literature.